Permasalahan dan Solusi Untuk Meningkatkan Kompetensi dan Kualitas Guru: Sebuah Kajian Pustaka - Mariana Ulfah Hoesny; Rita Darmayanti (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
This study aims to discuss about teachers competence as well as solutions in giving teachers professional development program, especially in IR 4.0 era. Teachers are an important part in education system since they hold important role in increasing the quality of human resources. In addition, the demand on teachers professional development is also escalating in order to match the advance of technology, especially in Industrial Revolution 4.0 (IR 4.0). Unfortunately, it was found that there are still a lot of problems faced by teachers. Those problems are related to how they do their teaching as well as improving their competence to fit the need of students who are mostly milennials generation. Some problems of teachers that are identified such as the low quality of teachers competence, abundant task ini composing teaching documents and administrative jobs, the difficult curriculum content that must be implemented and many more. One of the solutions offered is joining online teachers development programs available via social media. Another solution is improving pre-service teachers education.